Cisgenics - A Sustainable Approach for Crop Improvement - Telem, R.S. (Bentham Science Publishers, 2013)
The implication of molecular biology in crop improvement is now more than three decades old. Not surprisingly, technology has moved on, and there are a number of new techniques that may or may not come under the genetically modified (GM) banner and, therefore, GM regulations. In cisgenic technology, cisgenes from crossable plants are used and it is a single procedure of gene introduction whereby the problem of linkage drag of other genes is overcome. The gene used in cisgenic approach is similar compared with classical breeding and cisgenic plant should be treated equally as classically bred plant and differently from transgenic plants. Therefore, it offers a sturdy reference to treat cisgenic plants similarly as classically bred plants, by exemption of cisgenesis from the current GMO legislations. This review covers the implications of cisgenesis towards the sustainable development in the genetic improvement of crops and considers the prospects for the technology.